A CASE STUDY OF JAVANESE EFL STUDENTS’ EXPERIENCES IN PRONOUNCING THE ENGLISH /V/ SOUND - Andira Rukmana Dewi; Bambang Yudi Cahyono (Universitas Muhammadiyah Metro, 2026)
The pronunciation of English sounds that are absent in learners’ first language often becomes a challenge for EFL students and may affect both linguistic performance and emotional responses. This study explored Javanese EFL students’ experiences in pronouncing the English /v/ sound, focusing on their awareness, feelings, challenges, and learning strategies. This study employed a qualitative approach using an intrinsic case study design. Using semi-structured interviews as the primary research instrument, data were collected from six Javanese undergraduate students majoring in English Education at a public university in East Java, Indonesia, and analyzed through Braun and Clarke's thematic analysis. The findings revealed that students’ awareness of the distinction between /v/ and /f/ developed gradually through explicit instruction and corrective feedback rather than natural acquisition. Most participants experienced anxiety, hesitation, and self-doubt when pronouncing the /v/ sound due to articulatory unfamiliarity and phonological transfer from Javanese, which does not contain the /v/ phoneme. To overcome these difficulties, students applied several strategies, including repetitive practice, self-monitoring, teacher feedback, and exposure to audiovisual materials. The study concludes that pronunciation difficulties are influenced not only by phonological differences between languages but also by learners’ emotional experiences. These findings imply that pronunciation instruction should integrate explicit feedback, emotionally supportive classroom practices, and multimodal learning activities to foster both pronunciation accuracy and learners' speaking confidence.